A co-authorship network-based method for understanding the evolution of a research area: A case of information systems research - Wei, Fangfang; Zhang, Guijie; Feng, Yuqiang; Liu, Luning; Shao, Zhen (Malaysian Journal of Library and Information Science, 2017)
A baseline assessment research output is beneficial for policy decision makers to promote research. This paper presents a co-authorship network-based method to quantify and describe the scholarly publishing of a certain research field. To make our analysis more precise, we firstly generalized the measures used in previous literatures into formulas and analyzed the significance of the measures. We then classified our study into overall, individual, institutional and international levels to make our analysis clearer and more reasonable. Finally, we conduct a research of the structure, characteristics and development trend of co-authorship network based on publication output in top three journals in the field of information systems from 1993 to 2012. By synthetical analysis, our research results are helpful to know the productivity patterns, trends of the published research and status of international collaboration in this field.